Analisis Yuridis Pelaksanaan Tanggung Jawab Sosial Perusahaan (CSR) di Indonesia - Dwi Rangga Prasetyo; Ilham Pakih; Rosandi Firmawan; Norma Fitria (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The implementation of Corporate Social Responsibility (CSR) in Indonesia is one of the important aspects in company management that focuses not only on financial profit, but also on contributing to social and environmental welfare. This article aims to analyze the implementation of CSR in Indonesia from a legal perspective, by highlighting the regulations that govern and their implementation in the business world. This study uses a normative approach by analyzing applicable laws and regulations, such as Law No. 40 of 2007 concerning Limited Liability Companies and other related regulations, as well as their implementation by companies in Indonesia. In addition, this article also discusses the challenges and obstacles faced by companies in carrying out their social responsibilities, as well as how CSR contributes to sustainable development and community welfare. The results of the study show that although there are regulations that require companies to implement CSR, there is still a misalignment in the implementation between large and small companies, as well as a lack of supervision of effective CSR implementation. Therefore, there needs to be an effort to increase legal awareness and strengthen the supervision mechanism to ensure that CSR provides maximum positive impacts on society and the environment.